ASAS-SN search for optical counterparts of gravitational-wave events from the third observing run of Advanced LIGO/Virgo. Issue 3 (1st November 2021) - de Jaeger, T; Shappee, B J; Kochanek, C S; Stanek, K Z; Beacom, J F; Holoien, T W-S; Thompson, Todd A; Franckowiak, A; Holmbo, S
ABSTRACT: We report on the search for electromagnetic counterparts to the nine gravitational-wave events with a >60 per cent probability of containing a neutron star during the third observing run (O3) of the Laser Interferometer Gravitational-Wave Observatory (LIGO)–Virgo Collaboration (LVC) with the All-Sky Automated Survey for SuperNovae (ASAS-SN). No optical counterparts associated with a gravitational-wave event were found. However, thanks to its network of telescopes, the average area visible to at least one ASAS-SN site during the first 10 h after the trigger contained ∼30 per cent of the integrated source location probability. Through a combination of normal operations and target-of-opportunity observations, ASAS-SN observations of the highest probability fields began within 1 h of the trigger for four of the events. After 24 h, ASAS-SN observed >60 per cent of total probability for three events and >40 per cent for all but one of the events. This is the largest area coverage to a depth of g  = 18.5 mag from any survey with published coverage statistics for seven of the nine events. With its observing strategy, five sites around the world, and a large field of view, ASAS-SN will be one of the leading surveys to optically search for nearby neutron star mergers during LVC fourth observation run (O4).